Experiences of Special Education Teachers in New York State During COVID-19 Remote Instruction - Colvin, Kimberly F.; Ellis-Robinson, Tammy G.; Young, Taja R. (Journal of the American Academy of Special Education Professionals, 2023)
This study documented the experiences, challenges, and perspectives of special education teachers in New York State during the COVID-19 period of remote instruction in the spring of 2020 and during the 2020-21 school year. An invitation to complete an online survey about their experiences was sent to a random sample of special education teachers. The responses from 38 participants addressed areas such as relationships and communication with families, technology integration, student success, student engagement, and the extent to which the mandates of students’ Individualized Education Plans were able to be met. Many of the participants reported on both the challenges and successes they had with technology; this included some new teaching techniques and technologies that they planned to continue to use after returning to in-person instruction. While they dealt with a variety of challenges, the teachers’ actions demonstrated professional competence and integrity during this period.